Distribution of age, gender and body weight in AMI patients in a tertiary care center of Eastern India - Khatua, Tanushri; Mandal, Tanima; Saha, Mita; Majumder, Biswajit (Asian Journal of Medical Sciences, 2021)
Background: The leading cause of death in the world is coronary heart disease (CHD). In India, CHD manifests almost a decade earlier than in Western countries. Gender differences play an important role in the pathophysiology of AMI. Body weight and family history are claimed to be the indicators of relative risk of mortality. Aims and Objective: To look for the age and gender distribution pattern in patients with recent diagnosed AMI and to find out the association of some of the risk factors like BMI, family history. Materials and Methods: A descriptive study was conducted in a tertiary care hospital with 50 recent diagnosed AMI patients of either sex as cases after considering the inclusion and exclusion criteria. The biochemical parameters were measured by validated methods. Results: On statistical analysis, 58% of total AMI cases occurred before 50 years of age; out of which 18% belong to 31 - 40 years, 40% belong to 41- 50 years. Out of total 50 AMI cases, 60% is male and 40% is female. Obesity seen in 14% cases and 56% is overweight; 16% having positive family history. Conclusion: The study indicates a trend of early age onset AMI. Increased body weight and positive family history can be the risk predictors. It is suggested that younger age males and premenopausal women should not be ignored regarding the risk of MI. Further studies are required for verification.